2005
DOI: 10.1093/jac/dkh536
|View full text |Cite
|
Sign up to set email alerts
|

Is there a pharmacodynamic need for the use of continuous versus intermittent infusion with ceftazidime against Pseudomonas aeruginosa? An in vitro pharmacodynamic model

Abstract: These results stress the importance of optimizing t >MIC, even at peri-MIC concentrations, of ceftazidime against resistant strains. Local prevalence of resistance justifies, on a pharmacodynamic basis, electing for continuous infusion versus intermittent administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 15 publications
6
37
0
3
Order By: Relevance
“…Giving the same daily dose as a short-term infusion q6h instead of q8h achieved only a PK-PD MIC breakpoint of 2 mg/liter in CF patients. This prediction is in excellent agreement with the better outcome for CF patients with resistant or intermediate isolates when they received continuous ceftazidime infusion compared to when they received short-term infusion (both coadministered with tobramycin) (36,63) and with results from in vitro PD models (1,20,51).…”
Section: Discussionsupporting
confidence: 66%
“…Giving the same daily dose as a short-term infusion q6h instead of q8h achieved only a PK-PD MIC breakpoint of 2 mg/liter in CF patients. This prediction is in excellent agreement with the better outcome for CF patients with resistant or intermediate isolates when they received continuous ceftazidime infusion compared to when they received short-term infusion (both coadministered with tobramycin) (36,63) and with results from in vitro PD models (1,20,51).…”
Section: Discussionsupporting
confidence: 66%
“…Intermittent ceftazidime administration might result in undesirably high C max s and low, potentially sub-MIC C trough s, whereas the administration of ceftazidime by CI should avoid these fluctuations and keep the percentage of the time that the concentration is greater than the MIC above 100% for the entire duration of treatment (1,16,29). Moreover, Alou et al have stressed the importance of optimizing the time that the concentration of ceftazidime is greater than the MIC for resistant strains (1): they found no difference in the activities against susceptible and intermediate strains achieved by intermittent infusion and CI regimens, whereas only the CI achieved comparable activity over the same time period, minimizing the differences between the activities of the regimens against resistant and susceptible strains.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated an SD for the change in FEV 1 between the start and the end of each treatment of 12% (31). The regimens were regarded as equivalent if the difference in the change in FEV 1 (by use of the 90% confidence interval) between treatments was less than 5% of the predicted normal FEV 1 . We estimated that with 120 patients randomized, the study would have an 82% power to deem the regimens equivalent if they were truly identical.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For beta-lactams, it has been demonstrated that the stationary concentration (concentration at which killing equals growth) is close to the MIC and that regrowth occurs when the concentration falls below the MIC (9). Bactericidal activity against resistant strains and a higher probability of in vivo microbiological success have been reported with tϾMICs of 90 to 100% (1,2,14). Such pharmacodynamic observations provide a rationale for using continuous antibiotic infusions (10,12,13).…”
mentioning
confidence: 95%